2013
DOI: 10.1002/sej.1156
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Organizational Virtue: an Examination of Virtue Rhetoric, Country‐Level Corruption, and Performance of Foreign IPOs from Emerging and Developed Economies

Abstract: Extending signaling theory by discussing rhetoric in terms of cost and observability, we examine the relationship between organizational virtue rhetoric in prospectuses and the performance of foreign IPOs from 35 different countries. We also explore how the nature of this relationship is contingent upon the level of perceived corruption for each IPO firm's home country, a pervasive and costly problem for emerging economy countries due to its impact on economic growth and national governance. Our results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
120
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 133 publications
(157 reference statements)
0
120
1
Order By: Relevance
“…While most signaling theory addresses costly signals, some researchers (see Farrell & Rabin, 1996;Almazan, Banerji, & DeMotta, 2008;Payne et al, 2013) have observed that cheap talk, or less costly signals, can also be used by senders to reduce information asymmetries between parties. While on the surface it might seem that the entrepreneurial narratives on the Kiva.org Web site are costless signals, we argue that these signals can carry significant costs.…”
Section: Signaling Theorymentioning
confidence: 98%
“…While most signaling theory addresses costly signals, some researchers (see Farrell & Rabin, 1996;Almazan, Banerji, & DeMotta, 2008;Payne et al, 2013) have observed that cheap talk, or less costly signals, can also be used by senders to reduce information asymmetries between parties. While on the surface it might seem that the entrepreneurial narratives on the Kiva.org Web site are costless signals, we argue that these signals can carry significant costs.…”
Section: Signaling Theorymentioning
confidence: 98%
“…A similar ambiguity is present in other studies (e.g. Bruton et al, 2009;Hsu and Ziedonis, 2013;Payne et al, 2013;Sundaramurthy et al, 2014). The ambiguity weakens the clarity of argument.…”
Section: Information Asymmetry Between Which Parties?mentioning
confidence: 64%
“…More specifically, CATA is a particular type of content analysis in which word lists containing words and phrases that exemplify a specified construct are used to classify rhetoric accordingly (Duriau, Reger and Pfarrer, 2007). CATA has become commonplace among entrepreneurship and family business scholars, who have used the technique to examine a variety of strategic orientations, including EO (Short et al, 2009(Short et al, , 2010, market orientation (Zachary et al, 2011), long-term orientation (Brigham et al, 2014), organisational ambidexterity (Allison, McKenny and Short, 2014;Moss, Payne and Moore, 2014;Uotila et al, 2009), and organisational virtue orientation (Payne et al, , 2013.…”
Section: Dependent Variable: Eomentioning
confidence: 99%
“…Resulting values were then standardised by dividing the number of words and phrases identified in each document by the total number of words in each document, yielding a percentage of innovativeness, proactiveness, and risk-taking rhetoric in each document, respectively. This standardisation technique is advised because the length of shareholder letters varies significantly across observations, and thus is quite common in extant research Moss, Neubaum and Meyskens, 2015;Payne et al, 2013). Finally, once standardised values were calculated, we summed these values for each observation, yielding a composite measure of EO.…”
Section: Dependent Variable: Eomentioning
confidence: 99%